2005
DOI: 10.1007/s10531-004-0473-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological degradation of pentane by immobilized cells of Arthrobacter sp.

Abstract: The increasing production of several plastics such as expanded polystyrene, widely used as packaging and building materials, has caused the release of considerable amounts of pentane employed as an expanding agent. Today many microorganisms are used to degrade hydrocarbons in order to minimize contamination caused by several industrial activities. The aim of our work was to identify a suitable microorganism to degrade pentane. We focused our attention on a strain of Arthrobacter sp. which in a shake-flask cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Gambar 1A menunjukkan bahwa isolat LBF-1-0025 memiliki kemampuan optimal mendegradasi senyawa pentana pada konsentrasi 150 ppm dengan nilai OD 600nm sebesar 1,99. Konsentrasi optimal dalam pertumbuhan bakteri menunjukkan batas kemampuan bakteri yang dapat menggunakan senyawa pentana sebagai sum ber karbon dan energi untuk kegiatan metabolisme (degradasi substrat) (Ionata, Blasio, & Cara, 2005). Nilai OD 600nm sel isolat LBF-1-0025 meningkat dari 1,77 pada konsentrasi pentana 100 ppm menjadi 1,99 pada konsentrasi pentana 150 ppm.…”
Section: Hasil Dan Bahasan Optimasi Konsentrasi Pentana Bagi Pertumbuunclassified
“…Gambar 1A menunjukkan bahwa isolat LBF-1-0025 memiliki kemampuan optimal mendegradasi senyawa pentana pada konsentrasi 150 ppm dengan nilai OD 600nm sebesar 1,99. Konsentrasi optimal dalam pertumbuhan bakteri menunjukkan batas kemampuan bakteri yang dapat menggunakan senyawa pentana sebagai sum ber karbon dan energi untuk kegiatan metabolisme (degradasi substrat) (Ionata, Blasio, & Cara, 2005). Nilai OD 600nm sel isolat LBF-1-0025 meningkat dari 1,77 pada konsentrasi pentana 100 ppm menjadi 1,99 pada konsentrasi pentana 150 ppm.…”
Section: Hasil Dan Bahasan Optimasi Konsentrasi Pentana Bagi Pertumbuunclassified
“…Pentane-degrading Arthrobacter sp. was immobilized on a macroporous polystyrene particle matrix by promoting flocculation with the addition of Ca 2 at the end of the growth phase 4) . Earlier studies in our lab for fatty-oil containing wastewater treatment have shown that a bacterial consortium in an activated sludge formed into a biofilm showed good physical adsorption on polyurethane foam even with large pore size 5) .…”
Section: Introductionmentioning
confidence: 99%